Water table fluctuation and carbon dioxide emission from a tropical peat soil cultivated with pineapples (Ananas comosus L. Merr.) - Luta, W.; Ahmed, O. H.; Heng, R. K. J.; Choo, L. K. N. (International Network for Natural Sciences, 2017)
Tropical peat land is an important buffer for climate change as it absorbs atmospheric carbon and stores large carbon reserve. Inappropriate drainage and agricultural development on peat land results in GHG emissions such as CO2 and CH4which could shift the peat land ecosystem from carbon sink to carbon source. The objectives of this study were to: (i) quantify CO2 loss in a tropical soil under simulated water table fluctuation and (ii) determine the relationship between depth of water table and CO2 loss of a tropical soil cultivated with pineapples. Soil CO2 emission was captured using closed chamber method in field lysimeter and quantified using gas chromatography. It was carried out in July (dry month) and December 2015 (wet month). The peat soil water table fluctuation did not significantly affect emission of CO2 in pineapple cultivation. For lower water table, 147.5 t CO2 ha-1 yr-1 was emitted in the dry month whereas for higher water table, 19.6 t CO2 ha-1 yr-1. In the wet month, CO2emission of the lower water table was 23.7 t CO2 ha-1 yr-1whereasfor high water tables the emission was 25.6 t CO2 ha-1 yr-1. Soil CO2 emission for the lower water table was higher than that of the high water table whereas the opposite was true for the higher water table because of increase in soil temperature in the dry month. Regardless of season and depth of peat soil water table, this study will provide significant understanding of the effect of water table management on carbon loss in peat soils under pineapple cultivation.